A Clinical Study of the N-Terminal pro-Brain Natriuretic Peptide in Myocardial Injury after Neonatal Asphyxia - Rui Zhu; Zhenhong Nie (Elsevier, 2016)
We aimed to study the changes of serum N-terminal pro-brain natriuretic to peptide (NT-proBNP) levels after asphyxia-induced myocardial injury in children and explore the relationship between serum NT-proBNP levels and neonatal asphyxia. Methods: One hundred and six cases of neonatal asphyxia were randomly selected for the study, including 46 severe cases with myocardial injury and 60 mild cases with no cardiac injury. Sixty-three healthy newborns were selected as the control group. The serum NT-proBNP level was detected using electrochemiluminescence. Creatine kinase MB (CK-MB) and serum sodium and calcium were measured simultaneously. Results: The serum NT-proBNP level in the myocardial injury group was significantly higher than that of the noncardiac injury and control groups (p < 0.01). Asphyxia serum NT-proBNP and cardiac enzymes were significantly correlated. The median value of neonatal NT-proBNP was 1491 pg/mL at postnatal Day 3 (P3) and 1077 pg/mL at postnatal Day 14 (P14). The cutoff value for children with myocardial injury was 3612.5 pg/mL; the area under the receiver operating characteristic curve was 0.80 (p < 0.001), with a sensitivity of 83.3%, a specificity of 80.5%, a positive predictive value of 82.8%, and a negative predictive value of 79.4%. After treatment, the serum NT-proBNP level in children with myocardial damage showed a significant decrease. Conclusion: The serum NT-proBNP level can reflect myocardial injury in neonates with asphyxia and can guide its diagnosis.